The Historical Study of Prostitution Practices and Its Fiqh Analysis - Moh Ashif Fuadi; Moh. Mahbub; Irma Ayu Kartika Dewi; Martina Safitry; Sucipto Sucipto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
The practice of prostitution in Indonesia occurred from the time of the kingdom until after independence. In this country, prostitution is illegal, and the practice still exists today; prostitution is sexual activity between sellers and buyers in pleasure in the form of money or goods. This study will explain the historical study of prostitution in Indonesia. Through a qualitative approach, collecting relevant sources of books, articles, and online media supported by a historical-sociological approach This research results in that prostitution has long appeared, including during the time of the Prophet Muhammad. In the Prophet's time, there was still a practice of adultery narrated in the hadith that a woman complained to the Prophet that she committed adultery and wanted to be punished. The practice of sexual exploitation also occurs during the working period of Islamic Mataram through the King's concubine, who religiously must not exceed the four legal wives. Likewise, in the Dutch and Japanese, there was also prostitution. Several factors cause women to get caught up in the world of prostitution that is the most powerful there are economic factors. In normative boxing, all scholars or ulama agree that the practice of adultery through anything including localization or illegal prostitution, but in the view of the social jurisprudent, KH Sahal Mahfudz argues that localization can be a way out by eliminating it gradually and minimizing the greater negative impact.